Determination of metal ions in natural waters by flame-AAS after preconcentration on a 5-amino-1,3,4-thiadiazole-2-thiol modified silica gel. - Padilha, P. D.; Gomes, LAD; Padilha, CCF; Moreira, J. C.; Dias, N. L. (Marcel Dekker Inc, 1999)
5-amino-1,3,4-thiadiazole-2-thiol groups attached on a silica gel surface have been used for adsorption of Cd(II), Co(II), Cu(II), Fe(III), Ni(II), Pb(II) and Zn(II) from aqueous solutions. The adsorption capacities for each metal ion were (in mmol.g(-1)): Cd(II)= 0.35, Co(II)= 0.10, Cu(II)= 0.15, Fe(III)= 0.20, Hg(Il)= 0.46, Ni(II)= 0.16, Pb(II)= 0.13 and Zn(II)= 0.15. The modified silica gel was applied in the preconcentration and quantification of trace level metal ions present in water samples (river, and bog water).
Keywords: preconcentration; 5-amino-1,3,4-thiadiazole-2-thiol modified silica gel; water analysis